Experimental and Numerical Investigation of One-Dimensional Electroosmotic Consolidation Based on Segment Inheritance Strategy - Xiaoyu Yang; Meijuan Pei; Yongbin Xie; Xinhai Zhou; Xuguang Dong (Advances in Civil Engineering)
The attenuation of effective potential is a significant factor leading to the low postdrainage efficiency in the electroosmotic consolidation and drainage methods. In this study, the influence of the attenuation of effective potential on the electroosmotic consolidation process and the problem of solving the governing equations were investigated. A 102.5-hr one-dimensional electroosmotic consolidation test was performed to monitor the changes in the properties of the soil interior and the soil–electrode interface, and the variation curve of the effective potential in the test model was measured. The time-dependent nature of the potential distribution due to the attenuation of effective potential contradicts the assumption of introducing intermediate variables. To address this key issue, the variation curve of the effective potential was linearly segmented, ensuring the validity of introducing intermediate variables within each local state segment. Based on the continuity between state segments, the initial conditions of the governing equations in different state segments were updated, thereby extending the differential iteration within local state segments to the entire electroosmotic time domain. A finite-difference program for this method was developed using the Python language. Calculations and analyses based on the measured potential data were performed, revealing that a decrease in potential leads to a reduction in the effectiveness of electroosmotic drainage and consolidation in terms of the instantaneous distribution of pore pressure and the overall average degree of consolidation. This method can reflect the influence of the attenuation of effective potential on the pore water pressure during the electroosmotic consolidation process. The research findings of this paper can provide theoretical and numerical support for the improvement and engineering application of the electroosmotic consolidation and drainage method.